Biochar-fertilizer interaction increases nitrogen retention, uptake and use efficiency of cinnamomum camphora: A 15N tracer study - Guo, Yuxuan; Samson, Victor Manna; Zhi, Yetong; Chen, Yulin; Yang, Xi; Jia, Guanghao; Mao, Yanling (Geoderma Regional, 2025)
The excessive application of nitrogen (N) fertilizers can have detrimental environmental and economic impacts. Enhancing N use efficiency (NUE) through biochar application may help mitigate these losses while promoting plant growth. However, different biochar types may influence NUE differently. To investigate these effects, a greenhouse pot experiment was conducted to assess the impact of two biochar types on N dynamics. Four treatments were applied: control (CK), fertilizer (F), sawdust biochar + fertilizer (SBF), and rice straw biochar + fertilizer (RBF). A 15N tracer technique was used to evaluate N accumulation and NUE in C. camphora. Results indicated that biochar-fertilizer combinations significantly improved soil inorganic N (NH4+-N and NO3−-N) retention, this was attributed to biochar's high surface area and functional groups enhancing N ion sorption. Additionally, biochar-amended treatments (RBF and SBF) increased soil total N, 15N content and plant N uptake. Notably, by the final sampling period, plant total N content in the RBF treatment was 34.62 %, 16.67 %, and 9.38 % higher than in CK, F, and SBF treatments, respectively. Furthermore, 15N content in the RBF treatment was significantly greater than in SBF and F, showing increases of 26.51 % and 30.19 %, respectively. Biochar application also markedly improved NUE, with increases of 103.77 % and 27.86 % in RBF and SBF treatments, respectively, compared to the F. Similarly, soil fertilizer N recovery was 49.92 % and 43.94 % higher in RBF and SBF soils, respectively, than in F. The enhanced urease and protease activity in biochar-amended soils likely contributed to these improvements in fertilizer recovery and NUE. Overrall, our findings demonstrate that first the magnitude of N retention and NUE enhancement varies with biochar type. Second, combining biochar with fertilizer improves fertilizer N retention, NUE, and recovery, ultimately enhancing C. camphora productivity.